AMBIGUITAS HUKUM : PERATURAN KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET DAN TEKNOLOGI NO. 30 TAHUN 2021 - Sandiwan Putra Bintang Anugrah; Andyra Fathur Rizky; Ahcmad Maulana Rafit Arik (JOURNAL OF LAW AND NATION, 2024)
In the Unitary State of the Republic of Indonesia, society is predominantly composed of women. However, women of various ages, social statuses, and religions, who should be protected, often face sexual violence in their residential environments, workplaces, and educational settings. Higher education institutions, which are considered to provide costly education, also do not guarantee that their students are free from cases of sexual harassment. This phenomenon is a global issue occurring in many countries. In response to the increasing cases of sexual violence, the Ministry of Education and Culture issued Regulation of the Ministry of Education and Culture Number 30 of 2021 to protect students from threats of violence and sexual harassment. These cases cause mental and psychological disturbances, and it is only appropriate that the victims receive proper handling and not be further victimized by authorities on campus. This plan involves various parties, including students, lecturers, and educational staff. Universities have formed Task Forces for the Prevention and Handling of Sexual Violence to address these cases and conduct socialization and counseling through social media. It is hoped that with these steps, the academic community will have a better understanding of the prevention and handling of sexual violence.